Novel architecture of ternary ZnO/PMA/AgI heterojunctions towards boosted visible-light photocatalytic destruction of antibiotics - Yossor R. Abdulmajeed; Saad H. Ammar; Nada D. Ali; Fatma D. Ali; A. Al-Farraji; Marwa A. Lafta (Results in Surfaces and Interfaces)
Visible light-based photodegradation using heterojunctions has emerged as a suitable and environmentally friendly approach for removing antibiotic contaminants. The ease of transferring the photogenerated charges through heterojunctions to prevent their recombination is what makes the photocatalysis process an extremely successful process. Herein, we demonstrated that the constructed ZnO embedded with phosphomolybdic acid (PMA) and AgI ternary heterojunction (ZnO/PMA/AgI) considerably improves the visible-light-induced photocatalytic destruction activity toward levofloxacin (LEV) antibiotic (97.4% within 60 min) compared to binary samples (ZnO/PMA and ZnO/AgI) and single samples (ZnO, PMA, and AgI). Besides, 82% and 77.6% of initial chemical oxygen demand (COD) and total organic carbon (TOC) of real pharmaceutical wastewater sample have been removed over ZnO/PMA/AgI ternary heterojunction within 120 min. This achievement was attributed to the high redox properties of PMA as an effective electron transfer mediator between AgI and ZnO semiconductors. Moreover, the developed heterojunction facilitates the migration and separation of photoproduced charge carriers. Accordingly, the reaction mechanism of LEV degradation over ZnO/PMA/AgI heterojunction has been elucidated and supported by active-species capturing studies, which confirm that •O2−, and in less degree h+ were the main reactive species in the reaction. Besides, after six cyclic degradations, the degradation efficiency of the ZnO/PMA/AgI photocatalyst for LEV stayed about 90%, demonstrating its superb photocatalytic stability.